TSH Variability of Patients Affected by Differentiated Thyroid Cancer Treated with Levothyroxine Liquid Solution or Tablet Form. (9th May 2017) - Cappelli, Carlo; Pirola, Ilenia; Gandossi, Elena; Casella, Claudio; Lombardi, Davide; Agosti, Barbara; Marini, Fiorella; Delbarba, Andrea; Castellano, Maurizio
Abstract : Background. Recent guidelines from the American Thyroid Association (ATA) indicate that, in many patients affected by differentiated thyroid cancer (DTC), the serum TSH should be maintained between 0.1 and 0.5 mU/L. The purpose of this study was to evaluate the TSH variability of patients affected by DTC treated with liquid L-T4 formulation or in tablet form. Patients and Methods. Patients were eligible if (a) they were submitted to a total thyroidectomy and 131 I remnant ablation for DTC in our institution and (b) they were classified low-risk patients according to ATA guidelines 2009. Patients were randomized (1 : 1) to receive treatment of hypothyroidism with liquid L-T4 or tablet form. The first check-up evaluation was made from 8 to 12 months after 131 I remnant ablation. TSH values were established again after further 12 months. Results. A significant increase in TSH values (median) was observed in patients taking tablets [TSH (min–max): 0.28 (0.1–0.45) versus 0.34 (0.01–0.78) mIU/L, p = 0.041 ] as compared to those taking liquid formulation [TSH (min–max): 0.28 (0.1–0.47) versus 0.30 (0.1–0.55) mIU/L, p = 0.345 ]. Conclusions. The use of L-T4 liquid formulation, as compared to that of tablets, resulted in a significantly higher number of DTC patients maintaining TSH values in range for the ATA risk score, reducing TSH variability over the time.